(untitled) (The Pakistan Development Review, 2025)
• Focus on Investment, productivity, and exports. • Remove bottlenecks linked to terrifs, sludge: cost of regulation, financial & energy constraints. • Initiate “Regulatory Audit”. • Reduce bank’s holding of the government securities. • Create a National Debt Management Office. • Revisit DISCO’s management. • Introduce pre-paid metering. • Do away from uniform energy tariffs. • Introduce wheeling and bilateral agreements. • Tax Simplification • Implement Point of Sale (POS) • Deregulate the real estate market by eliminating NOCs and FBR/DC rates. • Tie Real estate & city development. • Unlock dead capital. • Internet for all. • Youth Involvement—promote sports, culture & clubs • Promote street vending—huge employment generation.